Development of diamond-like carbon films for large area microelectronic applications using ECR-CVD - Yoon, Soon Fatt. (2008)
In this project, the ECR-CVD technique has been used to deposit amorphous and diamond-like carbon films from a mixture of hydrogen and methane, and for the characterisation of optical, structural and mechanical properties of the films, the following analytical techniques has been employed.